Homozygous missense mutation L673P in adenylate kinase 7 (AK7) leads to primary male infertility and multiple morphological anomalies of the flagella but not to primary ciliary dyskinesia. (22nd January 2018) - Lorès, Patrick; Coutton, Charles; El Khouri, Elma; Stouvenel, Laurence; Givelet, Maëlle; Thomas, Lucie; Rode, Baptiste; Schmitt, Alain; Louis, Bruno; Sakheli, Zeinab; Chaudhry, Marhaba; Fernandez-Gonzales, Angeles; et al.
Abstract: Motile cilia and sperm flagella share an extremely conserved microtubule-based cytoskeleton, called the axoneme, which sustains beating and motility of both organelles. Ultra-structural and/or functional defects of this axoneme are well-known to cause primary ciliary dyskinesia (PCD), a disorder characterized by recurrent respiratory tract infections, chronic otitis media, situs inversus, male infertility and in most severe cases, hydrocephalus. Only recently, mutations in genes encoding axonemal proteins with preferential expression in the testis were identified in isolated male infertility; in those cases, individuals displayed severe asthenozoospermia due to Multiple Morphological Abnormalities of the sperm Flagella (MMAF) but not PCD features. In this study, we performed genetic investigation of two siblings presenting MMAF without any respiratory PCD features, and we report the identification of the c.2018T > G (p.Leu673Pro) transversion in AK7, encoding an adenylate kinase, expressed in ciliated tissues and testis. By performing transcript and protein analyses of biological samples from individual carrying the transversion, we demonstrate that this mutation leads to the loss of AK7 protein in sperm cells but not in respiratory ciliated cells, although both cell types carry the mutated transcript and no tissue-specific isoforms were detected. This work therefore, supports the notion that proteins shared by both cilia and sperm flagella may have specific properties and/or function in each organelle, in line with the differences in their mode of assembly and organization. Overall, this work identifies a novel genetic cause of asthenozoospermia due to MMAF and suggests that in humans, more deleterious mutations of AK7 might induce PCD.